REQUIREMENTS OF TEACHING ENGLISH FOR YOUNG LEARNERS: AN OVERVIEW IN PADANG, WEST SUMATERA - Rismareni Pransiska (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
People start communicates since they are babies. Language is a tool for communication. When a baby born, the environment influence what language she/he will use later on. At the first time, the baby acquires his/her mother tongue. Later on she/he learns other language. In Indonesia, especially in Padang, West Sumatera, children use Minang and Bahasa as their daily language. When the children enter early childhood education, English is also taught and introduced in kindergarten. Even though not all of Kindergarten in Padang put English as their subject, but most of “famous kindergarten” include English as their additional curriculum. They “sell” English as one of their program because they realize that many parents believe that English is an important thing in current and future for their children.  Basically, there are some requirement that need to be prepared in order to promote English as an holistic teaching and learning process.  This article discusses about some essential requirement in teaching English to young learner such as, curriculum, teacher competency, media and method used, and more specifically talks about its overview in Padang, West Sumatera.